Low-Temperature Aluminum-Aluminum Wafer Bonding. (24th August 2016) - Rebhan, Bernhard; Hinterreiter, Andreas; Malik, Nishant; Schjølberg-Henriksen, Kari; Dragoi, Viorel; Hingerl, Kurt
Abstract : Aluminum-aluminum thermo-compression wafer bonding is becoming increasingly important in the production of microelectromechanical systems (MEMS) devices. As the chemically highly stable aluminum oxide layer acts as a diffusion barrier between the two aluminum metallization layers, up to now the process has required bonding temperatures of 300°C or more. By using the EVG ® 580 ComBond ® system, in which a surface treatment and subsequent wafer bonding are both performed in a high vacuum cluster, for the first time successful Al-Al wafer bonding was possible at a temperature of 100°C. The bonded interfaces of blank Al wafers and Al wafers with patterned frames were characterized using C-mode scanning acoustic microscopy (C-SAM) and transmission electron microscopy (TEM) as well as dicing yield and pull tests representative for the bonding strength. The investigations revealed areas of oxide-free, atomic contact at the Al-Al bonded interface.